Gambaran Tingkat Pengetahuan Ibu Hamil tentang Vaksinasi Covid-19 di Wilayah Kerja Puskesmas Kalongan: Description Of The Level Knowledge Of Pregnant Women About Covid-19 Vaccination In The Working Area Of The Kalongan Health Center - Rika Nitya Arfiyaningsih; Umi Aniroh (Journal of Holistics and Health Sciences (JHHS), 2023)
Pregnant women are at risk of being infected with Covid-19 because they are the most vulnerable population to exposure. Pregnant women can protect themselves with vaccinations. Covid-19 vaccination provides protection to the mother and helps the fetus to have Covid-19 antibodies. According to data from the Kalongan Health Center, as much as 70.08% had received the vaccine and the rest had not been due to the lack of knowledge of pregnant women about vaccines. Sufficient knowledge will influence the decision of pregnant women to come to the health service unit to get the vaccine. This study aims to describe the level of knowledge of pregnant women about the Covid-19 vaccination in the Kalongan Health Center Work Area. This type of quantitative descriptive research. Time for research 22 November-15 December 2021. The sample technique in this study was a total sample with a total sample of 126 pregnant women. The instrument is a questionnaire. Data were analyzed univariately. The results showed that most of the respondents aged 20-35 years were 95.2%, >35 years 4.0% and <20 years only 0.8%. Elementary school education 5.6%, junior high school 37.3%, high school/vocational school 50.0% and university 7.1%. Being in the second trimester as much as 47.6% and 52.4% in the third. Primigravida mothers were 42.1% and multigravida 57.9%. The knowledge level of pregnant women about the Covid-19 vaccination was in the less category as much as 15.1%, 34.9% sufficient and 50% good. The level of knowledge of pregnant women about the Covid-19 vaccination in the Kalongan Health Center Work Area is in the good category of 50%. Suggestions for the Kalongan Health Center to provide health education to increase knowledge about the importance of the Covid-19 vaccination.   ABSTRAK Ibu hamil berisiko terinfeksi Covid-19 karena merupakan populasi paling rentan terpapar. Ibu hamil dapat melindungi diri dengan vaksinasi. Vaksinasi Covid-19 memberikan perlindungan pada ibu dan membantu janin memiliki antibodi Covid-19. Menurut data Puskesmas Kalongan sebanyak 70,08% sudah mendapatkan vaksin dan sisanya belum dikarenakan pengetahuan ibu hamil tentang vaksin yang masih kurang. Pengetahuan yang cukup akan mempengaruhi keputusan ibu hamil untuk  datang ke unit pelayanan kesehatan untuk mendapatkan vaksin.  Penelitian ini bertujuan untuk mengetahui gambaran tingkat pengetahuan ibu hamil tentang vaksinasi Covid-19 di Wilayah Kerja Puskesmas Kalongan. Jenis penelitian deskriptif kuantitatif. Waktu penelitian 22 November-15 Desember 2021.  Teknik sampel dalam penelitian ini adalam total sampel dengan jumlah sampel 126 ibu hamil. Instrumen berupa kuesioner. Data dianalisis secara univariat.  Hasil penelitian menunjukkan sebagian besar responden berusia 20-35 tahun sebanyak 95,2%, >35 tahun 4,0% dan < 20 tahun hanya 0,8%. Berpendidikan SD sebanyak 5,6%, SMP 37,3%, SMA/SMK 50,0% dan PT 7,1%. Berada pada trimester kedua sebanyak 47,6% dan ketiga 52,4%. Ibu primigravida sebanyak 42,1% dan multigravida 57,9%. Tingkat pengetahuan ibu hamil tentang vaksinasi Covid-19 dalam kategori kurang sebanyak 15,1%, cukup 34,9% dan baik 50%.  Tingkat pengetahuan ibu hamil tentang vaksinasi Covid-19 di Wilayah Kerja Puskemas Kalongan dalam kategori baik sebanyak 50%.  Saran bagi  Puskesmas Kalongan untuk memberikan  penyuluhan kesehatan untuk meningkatkan pengetahuan mengenai  pentingnya vaksinasi Covid-19.